The Least Significant Two-bit Substitution Algorithm for Image Steganography - Solak, Serdar; Altinişik, Umut (International Journal of Computer (IJC), 2018)
Steganography hides various data within different file types, which ensures secure communication. In recent years, the science of steganography has gained importance, due to the increase of large data on the internet and the safe transmission of these data. The main objective is to hide a large amount of data into the cover image in secure and incomprehensible manner. In this article, the two-bit least significant substitution (LSB) method is used to hide data on the colored cover images. In experimental studies, two-bit LSB substitution algorithm was performed in the form of LSB R2G2, LSB R2B2 and LSB G2B2 methods. In the classical LSB substitution method, the data are hidden in sequence, while the data are hidden by the shuffling algorithm at the proposed study. In this way, the security of hidden data is provided.